#TITLE_ALTERNATIVE# - Khairani NIM : 20214030, Rizki
This reaserch investigate the DNA-solvent interaction in the Peyrard-Bishop modelwhich focus on twisting and stretching DNA base pair motions. The dynamics ofthis system will be drawn from the solitary wave solution by using multiple scale expansion to the case of the vectorial lattice. The solvent effect is studied analyticallyand numerically, the breather-soliton is the solution for the stretching motionand the kink-soliton is the solution for the twisting motion. We found that the strength and the effective length the solvent interaction affect length and amplitude ofthe envelope. Solvent change the stability of the breath state (bubble formation) in the stretching motion. A positive value of solvent barier factor give the reshuffleof the base-pairs opening in stable condition moves to a positive value, means thehydrogen bond stretch. For twisting motion, we obtain the well of the kink-solitonafter adding the solvent, deeper than before, indicated the strand arc length which makes the DNA more winded, while a negative value gives the opposite effects.